Educational modernization in Spain in a scenario of social change and democratic openness. Conversations with Pedro Caselles Beltrán, General Director of General Basic Education (1976-1982) - Malheiro Gutiérrez, Xosé M. (Historia y Memoria de la Educación, 2021)
This text is an extract from several conversations held with Pedro Caselles Beltrán (1937), a primary school teacher with a degree in Philosophy and Humanities, specialising in Pedagogy, and an education inspector. Pedro Caselles occupied the provincial education offices in Lugo, Cádiz and A Coruña (1970-1976); later he was Deputy Director General of Non-State Schools and General Director of Basic Education (1977-1982). The text deals with his professional career, a summary of administrative management and political action, with particular emphasis on his time as a provincial delegate and later as a senior official in the Ministry of Education and Science (MEC). Under his mandate, several initiatives were carried out, including the promotion of the General Education and Financing of the Education Reform Act (LGE) of 4 August 1970 through the renewal of the Basic General Education Programmes.